The effect of organizational commitment and personal organizational fit on turnover intention of contract employees at PT Asia Bandar Alam Jakarta - Devy Sofyanty; Vera Agustina Yanti; Danny Ong; Suwantica Suwantica; Teni Agustina (Institute of Computer Science (IOCS), 2023)
Increasingly competitive business competition in the era of the industrial revolution 4.0 creates a competitive advantage. One of the company's efforts is to improve the quality of human resources, competing to provide good compensation for human resources. On the other hand, a number of things need to be of concern to companies related to HR. High turnover intention is a problem because they have to train new employees. Quantitative research method The sampling technique used is purposive sampling with 100 respondents. The sample is determined by considering certain characteristics the researcher has determined according to the research objectives. Characteristics of respondents in this study, namely: (1) status as contract employees; (2) Working period of fewer than 3 years; (3) Willing to be a respondent. The instrument used in this study was a questionnaire or questionnaire at PT Bandar Alam Jakarta. The study results show that organizational commitment negatively and significantly affects employee turnover intention. This means that the lower the employee's organizational commitment, the higher the employee turnover intention. Conversely, the higher the organizational commitment, the lower the employee turnover intention. The study results show that organizational commitment negatively and significantly affects employee turnover intention. This means that the lower the employee's organizational commitment, the higher the employee turnover intention. Conversely, the higher the organizational commitment, the lower the employee turnover intention.